Craving foods from social media: Which one to blame? For-you-page, followed culinary accounts, or friends who posted food content - Supit, Alva; Mamosey, Carmenita; Telew, Agusteivie (IHSA Institute, 2025)
In social media, food references may come from multiple sources, including algorithm-induced content (for-you-page, FYP), culinary accounts, and friends' posts. It is not known, however, which source exerted more effect on the food purchase decision. This study investigates the influence of social media on food purchasing behaviour among young adults, focusing on the impact of content exposure from these sources. A total of 73 respondents from the final year student population participated, predominantly female (mean age = 21.79 years). Results indicated that 76.7% of participants spent more than three hours daily on social media, with 94.5% exposed to culinary content from for-you pages (FYPs). Interestingly, while exposure to FYP content was massive, it did not significantly correlate with food purchases (p=0.138). Instead, content from followed culinary accounts and friends showed significant positive correlations (OR: 3.17 and 4.35, respectively; p<0.05) with purchasing decisions. After further analysis using binomial regression, only friends' posts persisted as a predictor for food purchases. The findings suggest that peer influence plays a crucial role in shaping food choices, highlighting the need for public health initiatives to promote healthier eating behaviours among young adults.